2020
DOI: 10.1097/ico.0000000000002575
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Effects of Pterygium and Pingueculum on the Ocular Surface and Efficacy of Surgical Excision

Abstract: Purpose: This systematic review examines the specific effects of pingueculum and pterygium on the ocular surface and evaluates the efficacy of surgical excision in reversing those effects. Methods: A systematic review was performed according to the Preferred Reporting Items for the Systematic Review and Meta-Analyses statement and included 59 articles studying the effects of pterygium and pingueculum on the ocular surface as measured by tear break-up ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
3
11
0
Order By: Relevance
“…12,13 Anti VEGF therapy causes the regression of blood vessels & prevents angiogenesis leading to a decrease in the size of Pterygium. 14,15 Although Pterygium has unclear pathogenesis, one of the important factors in its formation and progression is neovascularization. It has been proposed that a change in the ratio of an angiogenic stimulator to an inhibitor determines their development.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Anti VEGF therapy causes the regression of blood vessels & prevents angiogenesis leading to a decrease in the size of Pterygium. 14,15 Although Pterygium has unclear pathogenesis, one of the important factors in its formation and progression is neovascularization. It has been proposed that a change in the ratio of an angiogenic stimulator to an inhibitor determines their development.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, AMT also has its advantages, which can be bene cial in patients with ocular surface reconstruction, such as extensive conjunctival scarring and chemical injury or those who may require future glaucoma surgery [1,10]. A previous study showed that regardless of the surgical approach, the tear lm stability of patients after pterygium surgery is improved to varying degrees [13]. However, because the degree of tear lm stability improvement by the above two transplant means still showed con icting results [14][15][16][17][18][19][20], we conducted this meta-analysis to provide a more robust and accurate estimate of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with pterygium have disturbances in tear quality, quantity, and reduction of conjunctival goblet cell population [3]. One study showed that excision of pterygium could lead to an improved tear lm stability [13]. The main objective of this summary of our review is to report the comparison of tear lm stability after primary pterygium excision combined with LSCT or AMT based on the best available evidence.…”
Section: Introductionmentioning
confidence: 99%
“…1 Dry eye disease has been shown to be an important risk factor of pterygium development due to the increased tear osmolarity and chronic ocular surface inflammation. [2][3][4][5] The alternation of ocular surface-related parameters in pterygium has been extensively studied in recent years. The normal secretion of tears in eyes with pterygium revealed that the mechanism of its tear film instability was completely different from that of aqueous tear-deficient dry eye.…”
mentioning
confidence: 99%
“…The normal secretion of tears in eyes with pterygium revealed that the mechanism of its tear film instability was completely different from that of aqueous tear-deficient dry eye. [2][3][4][5] The similarities in incidence, gene signature, and severity between pterygium and meibomian gland dysfunction suggested that the reduced lipid layer thickness in pterygium may be a possible mechanism for tear film instability. 3,[5][6][7] However, a majority of previous studies have used control groups from the normal population.…”
mentioning
confidence: 99%